2018
DOI: 10.1590/0034-7167-2017-0342
|View full text |Cite
|
Sign up to set email alerts
|

Students’ knowledge of metabolic syndrome after educational intervention

Abstract: Objective: To analyze the knowledge of children and adolescents about risk factors for metabolic syndrome (MS) before and after educational interventions. Method: A quasi-experimental, comparative, prospective and intervention study conducted in 2015 and 2016 with 43 students in the city of Picos (state of Piauí-PI). Five health education meetings were held. For the knowledge analysis, was applied a questionnaire at three different moments. Results: Participants' mean age was 12.6 years (± 2.1), of which 60.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
2
0
6
Order By: Relevance
“…In a study conducted over a longer period of time and in the face-to-face modality, a divergent result was observed in relation to the present study. After an intervention with five EiH meetings related to the risk factors for MS, there was an increase in the level of knowledge after educational interventions, that is, the mean of the late post-test (90 days later) was higher than in the pre-test, with statistical significance (p<0.0001) 27 . In addition to that, the attitudes of changes after the educational interventions were evaluated, and it was found that 48.8% reported having managed to change eating habits and 62.8% of the students reported having introduced daily physical activity 27 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a study conducted over a longer period of time and in the face-to-face modality, a divergent result was observed in relation to the present study. After an intervention with five EiH meetings related to the risk factors for MS, there was an increase in the level of knowledge after educational interventions, that is, the mean of the late post-test (90 days later) was higher than in the pre-test, with statistical significance (p<0.0001) 27 . In addition to that, the attitudes of changes after the educational interventions were evaluated, and it was found that 48.8% reported having managed to change eating habits and 62.8% of the students reported having introduced daily physical activity 27 .…”
Section: Discussionmentioning
confidence: 93%
“…From this perspective, it is noteworthy that educational interventions increase the level of knowledge, contribute to the development of critical and reflective thinking, lead individuals to autonomy, capable of deciding and modifying attitudes with a view to self-care in health 28 . It is worth emphasizing the relevance of the continuity of the educational strategies, since changes in the life habits, such as adherence to healthy eating and practice of physical activity, occur in the medium-and long-term and result from individual dedication and professional assistance 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A Figura 3 apresenta: autor, ano, revista, objetivos, nível de evidência, tipos de intervenções educativas e desfecho. Foram publicados nos anos de 2002 (n=1) (16) , 2009 (n=4) (17)(18)(19)33) , 2010 (n=1) (20) , 2012 (n=1) (21) , 2013 (n=6) (23)(24)(25)(26)(27)(28) , 2017 (n=2) (29)(30) , 2018 (n=2) (9,31) e 2022 (n=1) (32) e classificados com nível de evidência II (n=11) (16)(17)(18)(20)(21)(23)(24)26,29,31,33) e III (n=8) (9,19,22,25,(27)(28)30,32) . Quanto à avaliação da qualidade metodológica, obteve 6/9 (n=3) (19,22,25) , 7/9 (n=5) (9,(27)(28)30,32) , 9/13 (n=3) (16)(17)26) , 6/13 (n=2) (18,23) , 7/13 (n=3) (20,…”
Section: Resultsunclassified
“…Os artigos foram analisados de forma descritiva e sintetizados em duas categorias, de acordo com o que é proposto na I Diretriz Brasileira de Diagnóstico e Tratamento da Síndrome Metabólica (3) , em: intervenções não medicamentosas e ou orientações no estilo de vida (9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) e orientações no estilo de vida, associadas ou não a intervenções medicamentosas (33) .…”
Section: Para Extração Dos Dados Foi Utilizado Ounclassified
See 1 more Smart Citation